Factors in removing job restrictions for cancer survivors in the United Kingdom Royal Air Force - Murray, K; Lam, K; McLoughlin, D; Sadhra, S (Springer, 2018)
Purpose To identify personal, occupational and clinical factors associated with the lifting of restrictions on duties among Royal Air Force (RAF) personnel who have returned to work after surviving primary cancer treatment. Methods A retrospective cohort of 205 RAF personnel aged 18–58 with cancer diagnosed between 2001 and 2011 was followed-up until May 2012. Personal, occupational, and clinical information was extracted from occupational health and primary care records. Predictors of the lifting of (a) employment restrictions on UK duties at 18 months after diagnosis and (b) the lifting of all deployment restrictions at the end of the study were analysed using logistic and Cox regression models. Results At 18 months, 62% of the cancer survivors had restrictions on their UK duties lifted. The positive independent predictors of unrestricted UK duties are testicular cancer (OR 5.34; 95% CI 1.21–23.6) and no treatment being required (16.8; 1.11–255.2). The lifting of all employment restrictions and return to full deployability was achieved by 41% of the participants (median time 2.1 years), with testicular cancer (HR 2.69; 95% CI 1.38–5.26) and age at diagnosis (1.05; 1.01–1.09) being the positive independent predictors of faster lifting of all restrictions. Conclusion Diagnostic group, prognosis and type of treatment are not the only predictor of employment outcome after cancer. Patient-centred factors such as smoking, age, fatigue, job status, job type and length of employment are also important predictors of return to pre-morbid job function in cancer survivors in the RAF.